Investigate on mechanism of nanofluid drainage gas recovery in tight gas reservoir. (27th January 2022) - Guowei, Qin; Qingping, Liu; Beilei, Zhang; Saisai, Sun; Yanzhao, Zheng; Wenlong, Qin; Mei, Wu
Abstract: Conventional drainage gas recovery and water-controlled gas recovery technologies are difficult to meet the needs of tight gas reservoirs. In order to solve this problem, nanofluid for drainage gas recovery was proposed to improve the effect of tight gas reservoir development. In this paper, the phase inversion method was used to prepare nanofluid with small particle size. Nanofluid could change the core surface characteristics, improve the drainage effect, and prolong its validity period. The influences of nanofluid on the gas-water flow in tight core and core surface properties have been systematically investigated by the experiments. The mechanism of the drainage gas recovery was discussed. The results showed that nanofluid with different mass concentrations can shift the isotonic point of gas-water relative permeability to the left (58.65%→54.78%@6.25 wt%, 56.49→54.66%@100wt%), reduce the irreducible water saturation (38.35→29.51%@6.25 wt%, 51.75→47.01%@100wt%), greatly increase the water relative permeability (63.79%@6.25 wt%, 100%@100wt%) and slightly reduce gas relative permeability (9.80%@6.25 wt%, 13.04%@100wt%), which has a significant drainage effect. A dense hydrophobic film was formed on the tight core surface to change its microstructure and wettability, which can achieve drainage gas recovery. Nanofluid will have a broad application in tight oil and gas reservoir stimulations.